2003
DOI: 10.5034/inquiryjrnl_40.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Community-Based Programs: A Longitudinal Analysis of State Variation in Expenditures and Utilization

Abstract: As states face challenges posed by budget crises and pressures to develop Medicaid home and community-based services (HCBS), this paper provides a longitudinal analysis of state variation in expenditures and utilization for three HCBS programs (waivers, home health and personal care), and for total Medicaid HCBS. The first part of the analysis describes the nature and scope of state variation for each program in 1999, using such measures as participants per 1,000 population and expenditures per capita. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…While findings on ethnicity have been mixed, a higher percentage of the nonwhite population has been shown to positively influence the provision of formal LTC programs, possibly as a result of higher rates of disability and poverty (Wallace et al 1998). Although there is some evidence that urban (metropolitan) residents are more likely to use (and therefore be provided with) formal HCBS compared with rural residents (Nyman et al 1991;Kenney 1993), recent work has found mixed effects (Kitchener, Carrillo, and Harrington 2003). Thus, this study included this variable without a hypothesis.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…While findings on ethnicity have been mixed, a higher percentage of the nonwhite population has been shown to positively influence the provision of formal LTC programs, possibly as a result of higher rates of disability and poverty (Wallace et al 1998). Although there is some evidence that urban (metropolitan) residents are more likely to use (and therefore be provided with) formal HCBS compared with rural residents (Nyman et al 1991;Kenney 1993), recent work has found mixed effects (Kitchener, Carrillo, and Harrington 2003). Thus, this study included this variable without a hypothesis.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Studies show the negative influence on Medicaid HCBS policy development of fiscally conservative state political climates as measured by the voting records of the states' U.S. senators Kitchener, Carrillo, and Harrington 2003). Thus, this study used the voting record of U.S. senators as a measure of state political climate with the expectation that stronger liberal records would be associated with personal care program adoption and expansion (Miller 2005).…”
Section: State Politicsmentioning
confidence: 99%
See 3 more Smart Citations